Politics of ideas and discourses in the prospective Bangsamoro political entity - Agojo, Kevin Nielsen M. (Animo Repository, 2018)
The Philippines has long been beset by internal armed conflicts within Mindanao, the country's second largest island. With the current Bangsamoro peace process, state institutions and non-state armed groups have been engaging in historic peace talks to achieve genuine peace within the conflict-ridden region. In reviewing recent developments in the peace process, however, noticeably lacking were in-depth discussions on the impact of the confluence of ideas and discursive interactions between major political actors in relation to the development of the Bangsamoro Political Entity (BPE) a prospective secular and democratic political unit that will replace the current Autonomous Region in Muslim Mindanao. This research study therefore seeks to determine the impact of the confluence of ideas and discourses between major political actors vis-à-vis the development of the BPE. In attaining the said objective, the study will first provide a discussion on the genealogy of the Bangsamoros quest for self-determination by tracing the dynamics of the ideational struggle that ensued between key actors in pursuit of their right to self-determination from pre-Spanish colonial rule up to the current period. It will be followed by an inductive thematic analysis of the three recent documents related to the peace process, namely the 2008 Memorandum of Agreement on Ancestral Domain, 2014 Bangsamoro Basic Law (BBL) draft, and the 2017 BBL draft. Using the said form of analysis, the study identified four areas of convergence or recurrent ideas in the said documents: ideas on intergovernmental relationship and governance structure; autonomy on fiscal and natural resource management; policing institution; and jurisdiction on ancestral domain. Two points of divergence or ideas that are classified under a similar theme but had its underlying principles modified were also discovered: one on the relationship between the BPE and its constituent local government units and another on its prospective executive authority. Government documents, secondary references, and interview data were utilized in discussing the abovementioned dynamics of the ideational struggle, areas of convergence, and points of divergence. The peace process is currently on its most crucial stage and thus, the actuality of the BPE is still uncertain. The Bangsamoro peoples quest and clamor for self-determination nevertheless will definitely continue whether it be on the negotiating table or through a return to armed warfare.